Gender Norms and Gender Equality in Full-Time Employment and Health: A 97-Country Analysis of the World Values Survey - Cislaghi, Beniamino; Bhatia, Amiya; Hallgren, Emma Sofia Thonander; Horanieh, Nour; Weber, Ann M.; Darmstadt, Gary L. (Frontiers in Psychology, 2022)
Background Almost nowhere in the world do women participate as much as men in the labor force. Despite differences in countries’ economic, social and cultural contexts, gender norms—unwritten rules of acceptable actions for men and women—have been found to affect women’s labor participation across contexts. Gender norms include those regulating who takes care of children, who is expected to earn more, and in which sectors men and women should work. Importantly, norms affect access to labor markets at times of scarcity: when there’s only work for one, gender norms can dictate whether a woman or man gets the job. Advocates of equal labor force participation point to evidence that employment can contribute to people’s health and well-being; yet the evidence is mixed and contradictory, and mostly comes from high-income countries. In restrictive normative contexts in which women are assigned the role of family caretaker, full time employment (FTE) might be particularly burdensome. At the same time, the literature lacks a cross-country analysis of how gender norms affect women’s FTE and their health when employed full time, despite qualitative research providing clear evidence of the influence of gender norms on labor participation. Aims In this paper we examine: (1) how gender norms affect women’s access to FTE across 97 countries; (2) associations between FTE and women’s self-reported health self-rated (SRH) across different normative contexts (i.e., countries where it is common vs. uncommon for women to stay home); and (3) how women’s FTE and gender norms changed over time in four countries. Data We used time-series data from the World Values Survey and European Values Survey conducted in over 100 countries between 1981 and 2014. Both surveys attempt to capture norms, beliefs and values in addition to sociodemographic information among a nationally representative adult population in each country. The sample for the cross-sectional analyses (aims 1 and 2) included 97 countries and 131,132 respondents. The sample for aim 3 included data from Argentina, Egypt, Finland and Japan. Variables Our outcome of interest was pro-equality norms in the context of access to the labor market for women. Respondents were asked “if jobs are scarce, men should have more right to a job than women do?”. Response options included no, neither or yes. We created a binary variable to represent pro-equality norms. We included employment status and SRH as exposures of interest. Analysis We used individual-level data to generate on-average and sex-stratified estimates of the outcome and exposures for each country, at each time point. We estimated the percentage of all respondents, of women, and of men who held pro-equality norms (believe that men should not have more right to a job than women), the percentage who were employed full time, and the average level of SRH. To measure gender inequality in FTE, we also estimated the absolute difference in FTE between women and men for each country at each time point. First, we conducted descriptive, cross-sectional ecological analyses using one survey per country from wave 5 or 6 (whichever was most recent) to examine associations between pro-equality norms and employment status as a proxy for associations between norms and the context of employment in each country. We also examined associations between pro-equality norms and SRH. We then specified adjusted logistic regression models with controls for age, sex and education to examine associations between pro-equality norms and employment status. To examine if the relationship between FTE and SRH varied by normative context, we grouped countries in quartiles of pro-equality norms. Finally, we conducted descriptive ecological analyses of the relationship between pro-equality norms and employment status over time in four countries. Results Objective 1: Gender norms intersect with socio-cultural contexts in determining women’s FTE. While in some countries gender norms aligned positively with women’s access to employment (i.e., more equal norms matched more equality in FTE), in Eastern Europe and South America we observed a mismatch. In Eastern Europe we found strong norms against equal access but small sex differences in FTE. In South America, we observed a stark difference in FTE favoring men, despite positive gender norms promoting women’s paid employment. Objective 2: We found the association between SRH and FTE to vary across normative contexts. For instance, while in Scandinavian countries it was protective to be a woman in FTE and harmful not to work full-time, we found the opposite effect in Middle Eastern countries. Objective 3: We found a general tendency to move toward greater equality in norms and FTE over time everywhere in the world. However, political and economic events can generate variations over time and setbacks in progress toward equality.We specifically looked at 4 countries: Argentina, Egypt, Finland and Japan and assessed the effects of economic, political and national legislative changes on FTE over time. Implications This paper contributes to the conversation on tensions between universal justice and contextual factors affecting one’s health. To achieve purposeful and global universal health and justice, policy makers and global health practitioners must design effective, context-relevant interventions that are deeply and transparently informed by the values they embody. As we strive to achieve global gender equality, its meanings and purposes will vary across contexts in ways that demand people-led conversations and interventions.